Use of a new antimicrobial consumption monitoring system (Vet-AMNet): Application to Dutch dairy sector over a 9-year period - Moura, Pedro; Sanders, Pim; Heederik, Dick; Van Geijlswijk, Ingeborg Marianne; Niza-Ribeiro, João (Frontiers in Veterinary Science, 2022)
The urgency of preventing the increase of antimicrobial resistance has been emphasized by international authorities such as World Health Organization, European Medicines Agency, and World Organization for Animal Health. Monitoring systems capable of reporting antimicrobial consumption data are regarded as a crucial pillar of this fight. The Vet-AMNet system was developed to collect and analyze national antimicrobial consumption data in Portuguese dairy farms to support the veterinary authority in stewardship actions and to assist both veterinarians and farmers in daily decisions related to antimicrobials. To evaluate the robustness of the system and other identified critical success factors, it was used to analyze antimicrobial consumption data available from the Dutch dairy cow sector over the period 2012 to 2020. The data previously used for publications by the Netherlands Veterinary Medicines Institute (SDa) were imported in the Vet-AMNet system and by comparing the output with the information generated by the system established in the Netherlands, the Portuguese system was validated. The analysis showed that the Vet-AMNet system can be adapted to different data sources and to the calculation of different metrics and can generate customizable dashboards in real time, by processing databases large enough to encompass country-wide AM monitoring programs. By compiling for the first-time antimicrobial usage data in the Dutch dairy sector during a nine-year period, this retrospective analysis also provided useful insights related to the dynamics and evolution of sectorial antimicrobial consumption against a background of a strong national antimicrobial policy initiated by public-private cooperation and supported by legislative measures.